Comissão intergestores bipartite microrregional em Minas Gerais: processo decisório e responsabilidade da gestão municipal em saúde - Aline Cerqueira Cruz (2011)
The collegiate instances of Unique Health System (SUS) are of great importance, since it is inthose spaces that the political and technical choices and confrontations take place. The realsituations are discussed in the Bipartite Inter-managerial Commissions (CIBs) and requiremultiple analyses, seeking to understand the role of managers and technicians in the constructionof strategies to improve the health of population. Creation of Macro and Micro regional CIBs inthe state of Minas Gerais, Brazil show the complexity of health systems organization, in order toguarantee the integrality of the actions. Ergo, to manage a city in this context is also a complextask, considering the specificities and the challenges of the work dynamics of a Municipal HealthSecretariat. For that reason, it is pertinent to study the decision making process of the CIBs, tobroaden the necessary knowledge to improve management and governance. This study aimed tounderstand the decision making process of a Micro regional CIB in the state of Minas Gerais,Brazil, and the adequacy of the decisions for the municipal health managements responsibilities.This is a qualitative case study, and this methodological approach made it possible to immerge inthe micro regional CIB of Minas Gerais, the centre of political decisions, diverse, complex andwith specificities in the managerial relations. The subjects of the research were six municipalhealth managers and three state representative subjects, members of the CIB, coming to a total ofnine subjects. Data was collected by observing the meetings and by semi-structured interviews,submitted to content analysis. The project was submitted to the Human Beings Research EthicsCommittee of University of Minas Gerais (COEP/UFMG) and the participants signed a waiver.Results show that the decision making process in the CIB analyzed takes us to a complex context,in which decisions must be consensual, according to the legislation. In situations in which there isnot an agreement between the managers, the case must be sent to the CIB / SUS MG. Decisionsare influenced by knowledge, interests, articulation ability and convincing of the involvedpersonnel, what generates different feelings related to the effective participation in the decisions.The micro CIB, considered, by the subjects, an important democratic space for collegiatedecision, has an important role, which is more for informing than deliberating. The micro CIBneeds to be reinforced as Regional Management Collegiate (CGR), as political arena withenough decision making power to promote the management of regional governance and network.In the micro CIB studied, it is possible to perceive that, in the current state, it still does not havethe dynamics and quality of integration process expected to a shared management, but there is aneffort to make joint discussions, in the most collective and participative way possible. It is alsopossible to perceive self-sufficiency in the secondary attention and services of tertiary attention.It is a differentiated micro region comparing to others of the State. However, there is still need ofimprovement in the monitoring, evaluation, and usage of SUS instruments planning in all aspectsconsidered.